Leadership sebagai Primary Forces dalam Meningkatkan Daya Saing Perguruan Tinggi - Kuncoro, Engkos Achmad (Bina Nusantara University, 2011)
Universities as an organization are always influenced by the dynamic external environment, in both national and global levels. Therefore, in order to maintain its competitiveness for its sustainability, the role of university as the center of knowledge and science, as well as the center of research and of Community Service shall continue to be competitive and ensure their sustainability growth. The purpose of this paper is an in depth study of factors influencing the competitiveness of universities in Indonesia. The method used in this work is using the review of the literature (studies Reader). Literature Review is intended to solve a problem which is basically based on the critical and comprehensive review of the relevant collection materials. Based on the study found that the aspects of leadership while Higher Education as a driving force to attempt the power of competitiveness strengths in order to escalate in the competition areas, and obtain results of competition result as expected by both terms based on students quality and quantity, adequate earning income, social and cultural attributes to the organizational image building.Â